ISLAMIC EDUCATION POLICY AND ITS IMPLICATIONS FOR EDUCATIONAL LEADERSHIP - Alifa Hanazahra; Junaidi (Yayasan Amanah Nur Aman, 2026)
Islamic education occupies a strategic position within the Indonesian national education system. Various government regulations, including Law Number 20 of 2003 concerning the National Education System and Law Number 18 of 2019 concerning Pesantren, have strengthened the legal foundation for the development of Islamic educational institutions. The effectiveness of these policies, however, is highly dependent on the quality of leadership within Islamic educational organizations. This study aims to analyze the role of leadership in formulating Islamic education policies, examine the relationship between government regulations and leadership in Islamic educational institutions, and explore the implications of national education policies for the management of Islamic educational organizations. The study employed a qualitative approach through library research by examining books, scientific articles, laws, and relevant policy documents. Data were analyzed using descriptive analytical techniques to identify patterns, relationships, and implications of policy implementation. The findings indicate that Islamic leadership characterized by vision, adaptability, consultation (shura), justice, and accountability plays a central role in policy formulation and implementation. Government regulations have encouraged institutional transformation toward professionalism, accountability, and quality assurance. At the same time, challenges emerge in the form of bureaucratization, regulatory dualism, and the potential erosion of Islamic institutional identity. Effective leadership serves as a bridge between national policy demands and the preservation of Islamic educational values. Therefore, the success of Islamic education policies depends largely on leadership capable of integrating modern management principles with Islamic values in a balanced and sustainable manner.